Wrist-ankle acupuncture attenuates cancer-induced bone pain by regulating descending pain-modulating system in a rat model - Chunpeng Zhang; Chen Xia; Xiaowen Zhang; Weimin Li; Xuerong Miao; Qinghui Zhou (BMC, 2020)
Abstract Background Cancer-induced bone pain (CIBP) presents a multiple-mechanism of chronic pain involving both inflammatory and neuropathic pain, and its pathogenesis is closely related to endogenous descending system of pain control. However, the action mechanism underlying the effects of wrist-ankle acupuncture (WAA) versus electroacupuncture (EA) on CIBP remains unknown. Methods Thirty-two Wistar rats were divided into sham, CIBP, EA-treated and WAA-treated groups. CIBP was induced in rats of the latter three groups. Time courses of weight and mechanical hyperalgesia threshold (MHT) were evaluated. After 6 days of EA or WAA treatment, the expressions of 5-hydroxytryotamine type 3A receptor (5-HT3AR) and μ-opioid receptor (MOR) in rostral ventromedial medulla (RVM) and/or spinal cord, as well as the levels of 5-HT, β-endorphin, endomorphin-1 and endomorphin-2 in RVM and spinal cord, were detected. Results Injection of cancer cells caused decreased MHT, which was attenuated by EA or WAA (P < 0.05). WAA had a quicker analgesic effect than EA (P < 0.05). No significant difference of MOR in RVM was found among the four groups. EA or WAA counteracted the cancer-driven upregulation of 5-HT3AR and downregulation of MOR in spinal cord (P < 0.05), and upregulation of 5-HT and downregulation of endomorphin-1 in both RVM and spinal cord (P < 0.05). β-endorphin and endomorphin-2 in RVM and spinal cord decreased in CIBP group compared with sham group (P < 0.05), but EA or WAA showed no significant effect on them, although a tendency of increasing effect was observed. Conclusion WAA, similar to EA, alleviated mechanical hyperalgesia in CIBP rats by suppressing the expressions of 5-HT and 5-HT3AR, and increasing the expressions of MOR and endomorphin-1 in RVM-spinal cord pathway of the descending pain-modulating system. However, WAA produced a quicker analgesic effect than EA, the mechanisms of which need further investigation.